Direct ink writing of hierarchically porous Al2O3 matrix composites with enhanced wettability of Al. (December 2022) - Ling, Qi; Yang, Li; Tang, Shiyan; Fan, Zitian; Liu, Xinwang; Jiang, Wenming
Abstract: Alumina (Al2 O3 ) ceramics have been successfully applied to many industrial fields, however, the poor wettability between alumina and metal limits its further application. In this work, SiC particles to generate reactive phase, and carbon particles (Cp ) to engender micro pores after sintering were introduced in direct ink writing hierarchically porous Al2 O3, and the wettability between Al2 O3 -based ceramic and molten aluminum was investigated. The results showed that the nanosized SiC shows superior reinforcement effect to the micron SiC and the addition of Cp improves the open porosity. Ceramic with Al2 O3 -50 nm SiC-Cp sintered at 1400°C possesses bending strength of 70.36 MPa and open porosity of 39.9 %. Compared with pure alumina ceramics, the contact Angle between composite ceramics and Al at 800 °C was reduced from 120° to 70°, which authenticates the enhanced wettability between metal and ceramic.